Multilateral Debt Relief Initiative : A First Assessment of Eligible Countries--Supplemental Information. (Policy Papers; Policy Paper ;, 2005)
This supplement summarizes new information available to staff since the issuance of The Multilateral Debt Relief Initiative: A First Assessment of Eligible Countries (December 8, 2005). It focuses on the six members (Ethiopia, Madagascar, Mauritania, Nicaragua, Rwanda, and Senegal) for which staff recommends that remedial actions be taken before the Board determines whether they qualify for debt relief from the Fund under the Multilateral Debt Relief Initiative.